2005
DOI: 10.1016/j.febslet.2005.03.049
|View full text |Cite
|
Sign up to set email alerts
|

Phoslactomycin targets cysteine‐269 of the protein phosphatase 2A catalytic subunit in cells

Abstract: According to the chemical genetic approach, small molecules that bind directly to proteins are used to analyze protein function, thereby enabling the elucidation of complex mechanisms in mammal cells. Thus, it is very important to identify the molecular targets of compounds that induce a unique phenotype in a target cell. Phoslactomycin A (PLMA) is known to be a potent inhibitor of protein Ser/Thr phosphatase 2A (PP2A); however, the inhibitory mechanism of PP2A by PLMA has not yet been elucidated. Here, we dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 32 publications
(42 reference statements)
1
54
0
Order By: Relevance
“…Although this covalent addition to fostriecin or cytostatin has not been experimentally verified, it was originally supported by the decreased affinity of 2,3-dihydrofostriecin (≥200-fold less potent than 2), 16 and confirmed with the more recent isolation and identification of the analogous Cys269 adduct with phoslactomycin (6). 17 Since the details of the fostriecin-PP2A model have not been disclosed elsewhere, it is presented herein alongside the newly generated cytostatin-PP2A model. Side-by-side overviews of the two models are presented in Figure 11 with space-filling representations of fostriecin and cytostatin.…”
Section: Models Of Cytostatin and Fostriecin Bound At The Pp2a Activementioning
confidence: 99%
“…Although this covalent addition to fostriecin or cytostatin has not been experimentally verified, it was originally supported by the decreased affinity of 2,3-dihydrofostriecin (≥200-fold less potent than 2), 16 and confirmed with the more recent isolation and identification of the analogous Cys269 adduct with phoslactomycin (6). 17 Since the details of the fostriecin-PP2A model have not been disclosed elsewhere, it is presented herein alongside the newly generated cytostatin-PP2A model. Side-by-side overviews of the two models are presented in Figure 11 with space-filling representations of fostriecin and cytostatin.…”
Section: Models Of Cytostatin and Fostriecin Bound At The Pp2a Activementioning
confidence: 99%
“…7,8 To determine the molecular target of such protein-reactive small molecules, a pull-down experiment utilizing a biotinylated molecular probe is effective. 9,10 Thus, based on our extensive SAR studies, 11 we designed a biotinylated derivative called GO-Y086, which has the GO-Y016-type substitution pattern (3,3 0 ,4,4 0 ,5,5 0 -hexasubstituted) with a biotin moiety connected at the 4 0 position via a linker.…”
mentioning
confidence: 99%
“…In addition, such antagonistic and agonistic compounds also provide useful lead compounds for drug discovery. In this context, we focused on the synthesis of dysiherbaine (37), neodysiherbaine A (38), and kaitocephalin (39). The total syntheses of dysiherbaine (37) and kaitocephalin (39) are presented here.…”
Section: Synthesis Of Glutamate Receptor Agonists and Antagonistsmentioning
confidence: 99%
“…In this context, we focused on the synthesis of dysiherbaine (37), neodysiherbaine A (38), and kaitocephalin (39). The total syntheses of dysiherbaine (37) and kaitocephalin (39) are presented here. 57,58) Dysiherbaine (37) was isolated by Sakai et al from the Micronesian sponge Dysidea herbacea and found to be a selective agonist of N-methyl-D-aspartate (NMDA)-type glutamate receptors.…”
Section: Synthesis Of Glutamate Receptor Agonists and Antagonistsmentioning
confidence: 99%
See 1 more Smart Citation